The relationship between Big Five Personality Traits, eating habits, physical activity, and obesity in Indonesia based on analysis of the 5th wave Indonesia Family Life Survey (2014) - Pristyna, Greena; Mahmudiono, Trias; Rifqi, Mahmud A.; Indriani, Diah (Frontiers in Psychology, 2022)
This study investigated the association between Big Five Personality Traits (Openness to new experience, Conscientiousness, Extraversion, Agreeableness, Neuroticism) and nutrition-related variables (eating habits, physical activity, and obesity using Body Mass Index). We used secondary data from the Indonesia Family Life Survey (IFLS) wave 5 involving total 14,473 men and 16,467 women aged 15-101 years (mean 37.34; SD 14.916) in Indonesia that selected by stratified random sampling conducted in the period 2014 to 2015. Data were collected through interviews with the Big Five Index 15 and a questionnaire similar to the Global Physical Activity Questionnaire which were translated into Indonesian, and measurements of height and weight. Analyses used binary logistic regression test controlled by socio-demographic factors (age, gender, education, occupation, and marital status) to determine the association between Big Five Personality Traits and eating habits (recommended and non-recommended foods), physical activity, and obesity. Results showed that openness and extraversion were positively associated with recommended and non-recommended foods, conscientiousness was positively associated with only recommended foods, agreeableness was positively associated with recommended foods and negatively associated with only one non-recommended food. Whereas, neuroticism was positively associated with non-recommended foods and negatively associated with recommended foods. Openness (p=0.010; OR=1.015; 95% CI=1.004-1.027) and conscientiousness (p<0.001; OR=1.045; 95% CI=1.030-1.059) were associated with physical activity. Conscientiousness (p=0.002; OR=1.025; 95% CI=1.009-1.041), extraversion (p<0.001; OR=1.079; 95% CI=1.065-1.092), and neuroticism (p<0.001; OR=0.966; 95% CI=0.953-0.978) were associated with obesity. Although some results were different from previous studies, these associations can be used as behavior change strategies due to the adaptation of personality characteristics can be modified even though the personality tends to be persistent. Further studies are needed to understand other mechanisms that might underlie this association.